2010
DOI: 10.1186/1471-2148-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Human evolution in Siberia: from frozen bodies to ancient DNA

Abstract: BackgroundThe Yakuts contrast strikingly with other populations from Siberia due to their cattle- and horse-breeding economy as well as their Turkic language. On the basis of ethnological and linguistic criteria as well as population genetic studies, it has been assumed that they originated from South Siberian populations. However, many questions regarding the origins of this intriguing population still need to be clarified (e.g. the precise origin of paternal lineages and the admixture rate with indigenous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 76 publications
2
50
0
1
Order By: Relevance
“…In addition, to further understand the genetic features and history of the ancient West Siberian people, information on the paternal and biparental gene lineages as well as additional ancestors from different periods would be very useful; however, the low rate of the successful samples analyzed in the present study may indicate the difficulty of obtaining nucleic DNA data, as reported in some previous studies. 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, to further understand the genetic features and history of the ancient West Siberian people, information on the paternal and biparental gene lineages as well as additional ancestors from different periods would be very useful; however, the low rate of the successful samples analyzed in the present study may indicate the difficulty of obtaining nucleic DNA data, as reported in some previous studies. 39,40 …”
Section: Resultsmentioning
confidence: 99%
“…More specifically, the decline in NRY diversity appears to be a domestication by-product, perhaps as a result of recent breeding programs aimed at producing valuable stallions for rural regions, as (i) the only Scythian horse sampled, dating to 2.8 KYA, exhibits an NRY haplotype different from that found in modern individuals (Lippold et al 2011b); and (ii) pedigree-based analyses can trace the most common patrilines back to a few, but extremely influential, stallions that lived 200 years ago (Wallner et al 2013). Only the Yakutian breed is known to display substantial levels of NRY diversity , probably because it originated in the 13th to 15th century, following the migration of Mongolian tribes to the Sakha Republic (Russia) (Pakendorf et al 2006;Crubézy et al 2010). This area has been traditionally isolated from main trade routes, such as the Silk Road, which acted as gene-flow corridors, shaping patterns of population differentiation in Eurasia (Warmuth et al 2013).…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%
“…North Central Asian (NCA) populations have been studied by many investigators but are underrepresented in more comprehensive population genetic surveys, such as the HGDP (Cann et al 2002;Rosenberg et al 2002;Li et al 2008) and non-recombining Y chromosome DNA (NRY)] (Chatters et al 2014;Duggan et al 2013;Fedorova et al 2013;Hertzberg et al 1989;Kemp et al 2015; Kitchen et al 2008;Kolman et al 1996;Lell et al 2002;Malyarchuk et al 2011;Malyarchuk et al 2013;Mulligan et al 2008;Nasidze et al 2005;Dulik et al 2012;Shi et al 2013;Starikovskaya et al 2004;Sukernik et al 2012;Raghavan et al 2014a;Volodko et al 2008;Zhong et al 2011;Zhong et al 2010), ancient DNA (aDNA, uniparental and autosomal) (Crubezy et al 2010;Keyser-Tracqui et al 2003, Keyser-Tracqui et al 2006Malyarchuk et al 2011;Raghavan et al 2014b). Mitochondrial DNA haplogroups offer a fairly crude inference of continental ancestry, conveying only information regarding possibly one or two top ancestry components while losing other ancestry information (Emery et al 2015).…”
mentioning
confidence: 99%